A Solar Rights Zoning Guarantee: Seeking New Law in Old Concepts - Glenn L. Reitze (Washington University Law Quarterly, 1976)
This Article will consider the problem of protecting access to sunlight, only one of the legal problems posed by the prospect of expanded use of solar energy. Two areas of law may provide helpful analogies for the development of law protecting access to sunlight: The first potential analogy is to natural resources law dealing with naturally mobile resources such as water, oil, and natural gas. The second analogy is to the law of access to and limitations on use of real property—both in the sense of conventional human access (as by a path), and in regard to access to daylight for windows. The latter might at first appear to offer an exact counterpart to the problem of protecting access to solar radiation for solar collection panels. As we shall see, however, the relationship is not so close as it might initially seem. This Article will then consider existing and proposed statutes designed to protect solar access rights, and will conclude with a new proposal.
Keywords: Easements; Energy resources; Zoning